Low cycle fatigue behaviour of Ti-13Nb-13Zr alloy in ultrasonic shot peened and stress relieved condition. (January 2023) - Kumar, Pramod; Mahobia, G.S.; Singh, V.; Chattopadhyay, Kausik
Highlights: Nano-structure up to 35 nm was developed on the surface of this alloy through ultrasonic shot peening treatment. Threefold increase in low cycle fatigue life was observed after 4 min of ultrasonic shot peening treatment. Sub-surface crack initiation was observed in ultrasonic shot peened fatigue tested samples. The principal mode of deformation in fatigue tested samples were dislocation slip and deformation twinning. Abstract: This study examined the effects of ultrasonic shot peening (USSP) and stress relieving treatment at 400 °C (USSP-SR) on low cycle fatigue behaviour of Ti-13Nb-13Zr alloy. The Un-USSP, USSP and USSP-SR samples were characterized for microstructure, surface roughness, hardness and low cycle fatigue. The surface microstructure of the USSP and USSP-SR specimens was refined to ∼ 35 nm. At strain amplitudes of 0.55 to 0.90 %, USSP nearly tripled fatigue life; however, the enhancement was lower in the stress relieved condition but still higher than Un-USSP, except at the highest strain amplitude of 0.90 %, where it was 20 % less than Un-USSP.